Komperatif Pemikiran Rahmah El-Yunussiyah Dan Mary Wollstonecraft Tentang Pendidikan Perempuan - Sumiyati; Munawaroh, Siti Qomariatul; Emilia Nurwati R; Kusuma, Hera Hapsari; Khoiriyah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to analyze and compare the educational thought of Rahmah El-Yunusiyyah and Mary Wollstonecraft on women’s education through philosophical and cognitive psychology approaches. Both figures played significant roles in advocating for women’s right to education, albeit within different cultural, religious, and socio-historical contexts. This research departs from the theoretical and social gap between Western concepts of emancipation and Islamic education, which are often perceived as incompatible. Employing a library research method and content analysis, the study examines Wollstonecraft’s major work, A Vindication of the Rights of Woman, as well as Rahmah El-Yunusiyyah’s ideas as reflected in the educational system of Diniyah Puteri Padang Panjang*. The findings reveal that both thinkers share a common vision in advocating education as a means of liberating women from cognitive and social marginalization. However, they differ in their epistemological foundations: Wollstonecraft’s framework is rooted in humanistic rationalism, whereas Rahmah emphasizes a synthesis of knowledge, faith, and morality. Theoretically, this study contributes to the philosophy of education by proposing an integrative paradigm that bridges Western rationality and Islamic spirituality. Practically, the findings provide a conceptual foundation for designing a holistic, contextual, and equitable model of women’s education in the global era.